(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This study aims to investigate the role of corporate social responsibility governance in reducing the carbon footprint of organizations. In an age of increasing environmental concerns and climate change, companies face increasing pressure to adopt sustainable practices. This research explores the relationship between the structure of government corporate social responsibility and the implementation of strategies to reduce carbon emissions. Taking into account various aspects such as regulatory policies, stakeholder engagement, and the integration of environmentally friendly technologies. Through a comprehensive analysis of existing literature, case studies, and empirical data, the research seeks to provide insight into the effectiveness of corporate social responsibility governance in promoting a more sustainable business environment. In order to achieve the objectives of the study, the researchers distributed (150) questionnaires to the employees of Al Waha Food Industry Co., Ltd. Important: CSR governance influences carbon footprint reduction and the effectiveness of CSR governance in reducing carbon footprint is likely to depend on a range of factors, including corporate commitment, government support, stakeholder engagement, and ability to overcome specific challenges. Industry. The most important of the recommendations presented here is: a corporate social responsibility policy must be formulated that clearly defines the company’s commitment to environmental sustainability, including goals and objectives for reducing carbon emissions.